Quality of Life With Pembrolizumab for Recurrent and/or Metastatic Head and Neck Squamous Cell Carcinoma: KEYNOTE-040. (14th May 2020) - Harrington, Kevin J; Soulières, Denis; Le Tourneau, Christophe; Dinis, Jose; Licitra, Lisa F; Ahn, Myung-Ju; Soria, Ainara; Machiels, Jean-Pascal H; Mach, Nicolas; Mehra, Ranee; Burtness, Barbara; Ellison, Misoo C; et al.
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) affects health-related quality of life (HRQoL); few treatments have demonstrated clinically meaningful HRQoL benefit. KEYNOTE-040 evaluated pembrolizumab vs standard of care (SOC) in patients with recurrent and/or metastatic HNSCC whose disease recurred or progressed after platinum-containing regimen. Methods: Patients received pembrolizumab 200 mg or SOC (methotrexate, docetaxel, or cetuximab). Exploratory HRQoL analyses used European Organisation for Research and Treatment of Cancer (EORTC) 30 quality-of-life, EORTC 35-question quality-of-life head and neck cancer-specific module, and EuroQoL 5-dimensions questionnaires. Results: The HRQoL population comprised 469 patients (pembrolizumab = 241, SOC = 228). HRQoL compliance for patients in the study at week 15 was 75.3% (116 of 154) for pembrolizumab and 74.6% (85 of 114) for SOC. The median time to deterioration in global health status (GHS) and QoL scores were 4.8 months with pembrolizumab and 2.8 months with SOC (hazard ratio = 0.79, 95% confidence interval [CI] = 0.59 to 1.05). At week 15, GHS / QoL scores were stable for pembrolizumab (least squares mean [LSM] = 0.39, 95% CI = –3.00 to 3.78) but worsened for SOC (LSM = −5.86, 95% CI = −9.68 to −2.04); the LSM between-group difference was 6.25 points (95% CI = 1.32 to 11.18; nominal 2-sided P = .01). A greater difference in the LSM for GHS / QoL score occurred with pembrolizumab vs docetaxel (10.23, 95% CI = 3.15 to 17.30) compared with pembrolizumab vs methotrexate (6.21, 95% CI = −4.57 to 16.99) or pembrolizumab vs cetuximab (−1.44, 95% CI = −11.43 to 8.56). Pembrolizumab-treated patients had stable functioning and symptoms at week 15, with no notable differences from SOC. Conclusions: GHS / QoL scores were stable with pembrolizumab but declined with SOC in patients at week 15, supporting the clinically meaningful benefit of pembrolizumab in recurrent and/or metastatic HNSCC.